A phenomenological approach to the institutionalisation of gender and development at the municipal level - Pangilinan, Lei A. (UP Los Baños Journal, 2018)
The study talks about gender issues and how the local government recognizes the need for Gender and Development. Its main interest is the Gender and Development (GAD) institutionalization at the municipal level. The aim is to evaluate how GAD programs are institutionalized. Specifically, the objective is to determine the level of GAD institutionalization using phenomenological approach and to identify the good practices and challenges of the selected municipalities in institutionalizing their GAD programs. The data for evaluation were gathered through interviews, document reviews, and focus group discussion. The study found out that the GAD that is being institutionalized in the municipalities does not have strong adherence to the true idea of Gender and Development. The GAD Plans and Budget are created for other priority projects of the current local government administration. In one municipality, non-GAD programs outnumber and outweigh GAD programs in terms of budget allocation while in the other, more efforts to promote GAD is noticeable since women empowerment is one of their major considerations in creating their GAD Plan. The study pointed out some good practices of the two municipalities in promoting GAD yet challenges are also identified since these are crucial in understanding the level of GAD institutionalization in the Local Government Units.